Modeling of the Caspian region energy system - Ayashev, K.; Akhmetbekov, Y.; Ibrayeva, A.; De Miglio, R. (Nazarbayev University, 2013)
This is the first instance when the Caspian Region fuel and energy complex is modeled with sufficiently detailed representation of both supply and demand sides (bottom-up approach). The technological description of the existing mix of plants, demand devices, industrial chains can be further improved, nevertheless there are several energy environmental actions that might be tested and evaluated using this model: • a cooperative implementation of energy commodity inter-trade across the four Countries and exports levels (quantities) of the Area as a whole; • the insertion of national-specific constraints aiming at stressing the systems on prospects of the renewable energy usages and on energy efficiency potential; • the insertion of a single environmental target for the whole area in the context of GHG reduction.
Keywords: first research week; Caspian region; energy system